2008
DOI: 10.1016/j.neuroimage.2007.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Age effects on hippocampal structural changes in old men: The HAAS

Abstract: Understanding the variability of the hippocampus in human brain research is essential. The effect of age on the hippocampus has been explored in several studies that have been focused on either normal aging or neural degeneration. Shape analysis of magnetic resonance imaging (MRI) provides morphological measures for brain structures. This study further investigates the age effects on hippocampal morphology in three groups (104 normal controls, 24 Alzheimer's disease (AD) and 14 vascular dementia (VaD) patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 72 publications
(112 reference statements)
6
18
2
Order By: Relevance
“…Most importantly, there is a remarkable lower level of left predominance in sham hypertensive controls (figures 2 and 3), compared with the high one observed in sham normotensive controls (figures 4 and 5). This is in agreement with the reduction of the asymmetry observed in prefrontal cortex and hippocampus in ADHD (Shaw et al, 2009) and during aging and vascular dementia compared to healthy subjects (Xu et al, 2008;Vallesi et al, 2010;Bergerbest et al, 2009). Indeed, disruption of physiological asymmetry has been involved in the pathogenesis of cognitive disorders such as ADHD.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Most importantly, there is a remarkable lower level of left predominance in sham hypertensive controls (figures 2 and 3), compared with the high one observed in sham normotensive controls (figures 4 and 5). This is in agreement with the reduction of the asymmetry observed in prefrontal cortex and hippocampus in ADHD (Shaw et al, 2009) and during aging and vascular dementia compared to healthy subjects (Xu et al, 2008;Vallesi et al, 2010;Bergerbest et al, 2009). Indeed, disruption of physiological asymmetry has been involved in the pathogenesis of cognitive disorders such as ADHD.…”
Section: Discussionsupporting
confidence: 87%
“…However, in ADHD, while the posterior component of this bilateral development was intact, the prefrontal one was lost (Shaw et al, 2009). The morphological asymmetry of hippocampus in healthy subjects, assessed by magnetic resonance imaging, is greater than that in Alzheimer's disease and in patients with vascular dementia (Xu et al, 2008). Studying the effects of age on the asymmetry of the motor system, Vallesi et al (2010) reported that older adults showed a more symmetric pattern than younger subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The above results support the view that there is possibly an increase in the vulnerability of temporolimbic brain structures to age-related changes in advanced stages of elderly life (most evidently in male subjects), and atrophy of such regions should be seen as compatible with normal brain aging. 27 rGM metabolic and volumetric decline in the hippocampus/parahippocampal gyrus is considered an important biomarker for the early detection of Alzheimer disease, 28,29 and it has been suggested that the presence of volumetric decline in limbic structures should be considered a sign of pathologic brain aging. 28,29 However, recently published structural and functional imaging studies reported findings that are consistent with the results described herein, 2,27,30 and the paucity of previous morphometric MR imaging studies specifically evaluating cognitively healthy subjects in the age range assessed in our study 7,27 may have reinforced the concept of medial temporal atrophy as necessarily denoting pathologic changes of the aging brain.…”
Section: Age-related Gm Changes In the Medial Temporal Regionmentioning
confidence: 99%
“…However, at the subcortical level, it was not until the advent of shape analysis techniques (e.g., Patenaude et al 2011) that successfully estimating regional shape variations in subcortical structures with high anatomical precision was possible. This approach has been mainly applied to unveil abnormal subcortical morphology in mental disorders or disease (Coscia et al 2009;Harms et al 2007;Kang et al 2008;McKeown et al 2008;Qiu et al 2008;Xu et al 2008) but recently also to understand the role of subcortical shape in high-order cognition in healthy populations (Burgaleta et al 2013b). …”
Section: Introductionmentioning
confidence: 99%